Poly cystic ovarian syndrome (PCOS) in Oman: effects in pregnancy, psychosocial aspects of infertility and quality of infertility care from patients’ and healthcare providers’ perspectives - AlSumri, H.S. (2019)
Background Poly cystic ovarian syndrome (PCOS) is a common endocrine problem among women of reproductive age. The estimated prevalence is 6-12% worldwide using the Rotterdam diagnostic criteria. A recent study showed a prevalence of 7% in Oman. Evidence is lacking about the association of PCOS and the reproductive health of women in the Middle East including Oman. Despite extensive research, it is still unclear whether PCOS carries an increased risk of adverse outcomes in mothers and their newborns. PCOS is also a common cause of anovulatory infertility. However, the psychosocial impact of infertility experienced by women with PCOS is a neglected research area. Studying the lived experience of infertility among Omani women is important, given the cultural context of the region where no evidence is yet available. Furthermore in attempting to evaluate fertility services it is vital to understand both patients’ and healthcare providers’ (HCPs) perceptions on the care provided in fertility clinics to identify ways in which this aspect of care could be improved.